Study of Islamic Education Thought in the Perspective of KH. Idham Chalid - Arief Rahman; Zulfa Jamalie (Transformatif, 2023)
Initially named Arabische School which was educated by KH. Abdurrasyid, then changed its name to Madrasah Rasyidiyah during the time of KH. Juhri Sulaiman. Furthermore, it changed to Ma'had Rasyidiyah during the time of H. M. Arif Lubis and at the time of KH. Idham Chalid changed to Normal Islam and Rasyidiyah Khalidiyah which held the principle of tafaqquh fi ad din (Normal Islam). KH Idham Chalid's efforts as the leader of the Pesantren at Normal Islam were to combine exact lessons and general science as support with a presentation of 60% religious lessons and 40% general lessons using Arabic as an introduction. Context related to the study of Islamic education thought and aspects of advancing Islamic education, especially during the struggle for independence of the Republic of Indonesia. This article uses a literature study with the type of research using qualitative, through this method the facts revealed include heuristic and historigraphy in revealing the history and role of KH. Idham Chalid in the world of education. The purpose of this research is to reveal patterns of thought in the development of Islamic education and the findings obtained are KH. Idham Chalid made reforms in the world of pesantren education related to three aspects, namely improving pesantren institutions, improving the education system, and developing infrastructure